La formation par compétences au Service de Police de la Ville de Montréal - Éné, Sabina (École nationale d'administration publique, 2008)
Keywords: Police

Évaluation de l'implantation d'un programme de formation des recrues du Service de police de la ville de Montréal intégrant l'approche par compétence et l'apprentissage par problèmes - Basmadjian, Virginie (École nationale d'administration publique, 2008)
Keywords: Police

Du képi au kippa: implantation des nouvelles politiques de rapprochement du service de police de la Communauté urbaine de Montréal en milieu hassidique - Shamlian, Isabelle (Université du Québec à Montréal, 2001)
Keywords: Hassidim; Juifs; Police

The Psycho-Sociological Impact to Inner City English Language Schools in Montreal Resulting from the Faulty Implementation of Public Policies - Martin, Cynthia Jean (Université Concordia, 2004)
Keywords: Anglophones

La professionnalisation de la Sûreté provinciale du Québec, 1960-1970 - Vézina, Jacques (Université du Québec à Trois-Rivières, 2002)
Keywords: Police

Pression policière et actes de défiance: une analyse de la résistance aux interventions policières à Montréal (1998-2008) - Boutet, Mylène (Université de Montréal, 2009)
Keywords: Police

Opinions et attitudes des policiers face à un changement organisationnel important - l'implantation du programme ACES au SPVM - Desbiens, Daniel (Université de Montréal, 2002)
Keywords: Police

La prise en charge pénale des personnes itinérantes: analyse de dossiers policiers - Campeau, Paule (Université du Québec à Montréal, 2002)
Keywords: Itinérance; Police

La contestation des espaces gais au centre-ville de Montréal depuis 1950 - Guindon, Jocelyn M. (Université McGill, 2001)
Keywords: Police; Quartiers

Diagnostic organisationnel de l'absentéisme chez les employés civils du SPVM pour les années 2005 à 2007 - Dufresne, Julie (École nationale d'administration publique, 2008)
Keywords: Police; Travail

La surveillance policière dans les bars de Montréal - Boivin, Rémi (Université de Montréal, 2007)
Keywords: Alcool; Police

Les dirigeants du SPVM, les chercheurs et les policiers arabo-musulmans: une étude sur l'institutionnalisation de la "diversité" - Lavoie, Danya (Université de Montréal, 2006)
Keywords: Arabes; Musulmans; Police

Jurys, participation civique et représentation au Québec et au Bas-Canada: les grands jurys du district de Montréal (1764-1832) - Fyson, Donald (Revue d'histoire de l'Amérique française, 2001)
issued: 2001-22-00
Keywords: Criminalité; Juges; Police

La ville de Montréal et la question des jeux de hasard et d'argent (1930-1970): crime organisé, corruption et financement municipal - Brodeur, Magaly (Université de Sherbrooke, 2008)
Keywords: Alcool; Criminalité; Police

Les opérations policières illégales: le rôle de l'expertise scientifique dans la Commission Keable, 1977-1981 - Guilbeault-Cayer, Émilie (Bulletin d'histoire politique, 2008)
issued: 2008-23-00
Keywords: Crise d'octobre; Droit; Front de Libération du Québec; Police

Cours de justice criminelle et classes ouvrières au tournant du XXe siècle à Montréal (1891-1921) - Aranguiz, Marcela (Université du Québec à Montréal, 2009)
Keywords: Cour de police de Montréal; Cour du Recorder de Montréal; Criminalité; Juges; Tribunaux

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens